Effect of Time Since Death on Multipathogen Molecular Test Results of Postmortem Specimens Collected Using Minimally Invasive Tissue Sampling Techniques. (15th December 2021) - Dawa, Jeanette; Walong, Edwin; Onyango, Clayton; Mathaiya, John; Muturi, Peter; Bunei, Milka; Ochieng, Washington; Barake, Walter; Seixas, Josilene N; Mayieka, Lillian; Ochieng, Melvin; Omballa, Victor; et al.
Abstract: Background: We used postmortem minimally invasive tissue sampling (MITS) to assess the effect of time since death on molecular detection of pathogens among respiratory illness–associated deaths. Methods: Samples were collected from 20 deceased children (aged 1–59 months) hospitalized with respiratory illness from May 2018 through February 2019. Serial lung and/or liver and blood samples were collected using MITS starting soon after death and every 6 hours thereafter for up to 72 hours. Bodies were stored in the mortuary refrigerator for the duration of the study. All specimens were analyzed using customized multipathogen TaqMan® array cards (TACs). Results: We identified a median of 3 pathogens in each child's lung tissue (range, 1–8; n = 20), 3 pathogens in each child's liver tissue (range, 1–4; n = 5), and 2 pathogens in each child's blood specimen (range, 0–4; n = 5). Pathogens were not consistently detected across all collection time points; there was no association between postmortem interval and the number of pathogens detected ( P  = .43) and no change in TAC cycle threshold value over time for pathogens detected in lung tissue. Human ribonucleoprotein values indicated that specimens collected were suitable for testing throughout the study period. Conclusions: Results suggest that lung, liver, and blood specimens can be collected using MITS procedures up to 4 days after death in adequately preserved bodies. However, inconsistent pathogen detection in samples needs careful consideration before drawing definitive conclusions on the etiologic causes of death.